Investigation of Linear Polarization for a Specimen Insulator of Scanning Electron Microscope in Sense of Mirror Efectronic Phenomenon - Al-Obaidi, Hassan N.; Mahdi, Ali S.; Khaleel, Imad H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
An analytical procedure has been carried out to measure the charge that may be trapped in an insulator sample of scanning electron microscope. It mainly concerns the determination of the deduced polarization charges by means of mirror effect phenomenon. Several relations related to such issue have been modified so as to be applicable for regarding charges due to polarization in linear and isotropic material. Consequently, the potential arises as a result for both trapped free and polarization charges which is set up. Actually the well-known magnification factor method is adopted to be a case study to implement the introduced approach. Results have clearly showed that the polarization charge significantly influences the Coulomb’s force that incoming electrons suffer from. Furthermore, the variation in the sample potential mainly depends on the dielectric constant of the specimen material.